Effect of spherical aberration on the coupling efficiency between a laser diode and a hemispherically lensed tapered fiber - Kumaran, S.; Faidz, A. R. (2004)
The objective of our work is to conduct a theoretical analysis to determine the coupling efficiency between a laser diode (LD) and a hemispherically lensed tapered single-mode fiber (SMF), which takes into account the effect of spherical aberration on the lens surface. The results obtained clearly show that our proposed theoretical method provides a good estimation of the experimental data. (C) 2004 Wiley Periodicals, Inc.